Intersection of nanomaterials and organoids technology in biomedicine - Shen, Chen; Zhang, Zi-jian; Li, Xiao-xue; Huang, Yun-peng; Wang, Yong-xiang; Zhou, Hui; Xiong, Li; Wen, Yu; Zou, Heng; Liu, Zhong-tao (Frontiers in Immunology, 2023)
Organoids are stem cell-derived, self-organizing, 3D structures. Compared to the conventional 2D cell culture method, 3D cultured organoids contain a variety of cell types that can form functional “micro-organs” and can be used to simulate the occurrence process and physiological pathological state of organ tissues more effectively. Nanomaterials (NMs) are becoming indispensable in the development of novel organoids. Understanding the application of nanomaterials in organoid construction can, therefore, provide researchers with ideas for the development of novel organoids. Here, we discuss the application status of NMs in various organoid culture systems and the research direction of NMs combined with organoids in the biomedical field.